Switching Regression Models with Imperfect Sample Separation Information–With an Application on Cartel Stability - Lee, Lung-Fei; Porter, Robert H. (Econometrica, 1984)
Lung-Fei Lee, Robert H. Porter, Switching Regression Models with Imperfect Sample Separation Information–With an Application on Cartel Stability, Econometrica, Vol. 52, No. 2 (Mar., 1984), pp. 391-418